Reduced ACTC1 Expression Might Play a Role in the Onset of Congenital Heart Disease by Inducing Cardiomyocyte Apoptosis - Jiang, Hong-Kun; Qiu, Guang-Rong; Li-Ling, Jesse; Xin, Na; Sun, Kai-Lai (Circulation Journal, 2010)
Background: The Cardiac α actin 1 gene (ACTC1) has been related to familial atrial septal defects. This study was set to explore a potential role of this gene in the formation of sporadic congenital heart disease (CHD). Methods and Results: Assessment of cardiac tissue samples from 33 patients with sporadic CHD (gestational age (GA) 18 weeks-49 months) with real-time RT-PCR, Western blotting and immunohistochemistry has revealed a markedly decreased ACTC1 expression in the majority of samples (78.8%) compared with autopsied normal heart tissue from aged-matched subjects (GA 17 weeks-36 months). Also, as shown by terminal deoxynucleotidyl transferase-mediated dUTP nick end-labeling (TUNEL) assay, the proportion of apoptotic cardiomyocytes in samples featuring down-regulated ACTC1 expression (Group 1) was significantly greater than those with normal expression (Group 2) and the controls (P<0.01). The proportion of apoptotic cells strongly correlated with the expression of ACTC1 (r=-0.918, P<0.01). A study of 2 essential genes involved in apoptosis, Caspase-3 and Bcl-2, confirmed that the former has significantly increased expression, whilst the latter has decreased expression in Group 1 than in the other groups (P<0.01). Transfection of a small interfering RNA targeting, Actc1 (Actc1-siRNA), to a cardiomyocyte cell line, H9C2, also detected more apoptotic cells. Conclusions: Reduced ACTC1 expression might play a role in the onset of CHD through induction of cardiomyocyte apoptosis. (Circ J 2010; 74: 2410-2418)